Occurrences of eggs and larvae of gastrointestinal nematodes in nails of street inhabitants in Dhaka City - Khanum, Hamida; Islam, Md Riajul; Parvin, Safia (Journal of Life and Earth Science, 2011)
This study was carried out during the months of May and August, 2008 to determine the prevalence of eggs and larvae of gastrointestinal nematodes in nails of children, mother, venders and rickshaw pullers in Dhaka city. Out of 120 individuals, 77 were infected with different nematodes and the prevalence was 64.16%. Ascaris lumbricoides infestation was positive for 39 persons (50.65%), Trichuris trichiura for 18 (23.37%) and Ancylostoma duodenale for 20 (25.97%). Prevalence of nematode parasites in left hand of children in the age group 2-4 years had the highest prevalence (80%) in comparison with the left hand of the rickshaw pullers (75.75%). The highest infection was 80% among the people who used to wash their hands with only water after defaecation, 72.22% who washed their hands with soil and water, and only 12.5% who washed with soap and water. It was also found that 61 peoples did not cut their nails regularly and the infection rate was 79.22%. On the other hand, those who cut their nails regularly, the infection rate were 37.20%. A higher rate of infestation was thus found to be associated with poor socioeconomic conditions, poor sanitation, poor ecological conditions, general ignorance, unawareness of personal hygiene and miscellaneous bad habits. Key words: Gastrointestinal nematodes; eggs and larvae; nails; street inhabitants; Dhaka City. DOI: 10.3329/jles.v5i0.7354 J. Life Earth Sci., Vol. 5: 75-79, 2010